Organo-f-Complexes for Efficient and Selective Hydroborations - Liu, Heng; Eisen, Moris S. (Synthesis, 2020)
Organo-f-complexes catalyzing small molecule transformations have been a hot topic in the past few years. Compared to other transformations, the hydroboration of C=X (X = C, N, O) unsaturated bonds serves as an important strategy to prepare organoborane derivatives, which are important intermediates in organic synthesis. This review outlines recent advances in organolanthanide and organoactinide complexes promoting the hydroboration of C=X containing substrates. After a brief introduction, three types of hydroboration will be presented: alkene hydroboration, carbonyl hydroboration, and imine and nitrile hydroborations. The catalytic performance, mechanism, and kinetic studies are discussed in detail, aiming to emphasize the catalytic differences between the diverse organo-f-catalysts. Additionally, challenges and future directions of this field are also presented.1 Introduction2 Alkene Hydroboration3 Carbonyl Hydroboration4 Imine and Nitrile Hydroboration5 Conclusions and Outlook
Keywords: organolanthanide; organoactinide; hydroboration; selective; alkene; imine; ketone; aldehyde